Creating Novel Strategies: Understanding Theory Development in Adult Learning - Sandria S. Stephenson (Adult Education Research Conference, 2010)
There are a numerous “theories” associated with adult learning and adult education. However, to date, there is not one single theory that adequately describes adult learning. Rather there are several theories, models, and frameworks used in advancing the ideologies of adult learning and the characteristics of the adult learner. This paper advances and table presentation advances the discussion about the elements of good theory development in the practice of adult education.